The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1136/jclinpath-2016-204294
|View full text |Cite
|
Sign up to set email alerts
|

Plasmablastic lymphoma versus plasmablastic myeloma: an ongoing diagnostic dilemma

Abstract: The distinction between plasmablastic lymphoma from plasmablastic myeloma warrants detailed knowledge of clinical, radiological and laboratorial findings. New studies identifying distinctive phenotypical or genetic features are needed to improve the histopathological differentiation of plasmablastic neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 29 publications
2
47
0
5
Order By: Relevance
“…The relationship of PBL with diffuse large B‐cell lymphoma (DLBCL) showing terminal plasma cell differentiation and extramedullary plasma cell tumours (PCTs) remains a diagnostic challenge. Reports have described similarities in clinical presentation, morphological appearances, and immunophenotypes; however, this distinction is significant, because the different entities vary in clinical course, prognosis, and management requirements . The presence of EBV‐encoded RNA significantly favours a PBL diagnosis (50–75%), although studies have shown that both immunocompetent and immunocompromised individuals may develop EBV‐driven extramedullary PCTs and DLBCLs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship of PBL with diffuse large B‐cell lymphoma (DLBCL) showing terminal plasma cell differentiation and extramedullary plasma cell tumours (PCTs) remains a diagnostic challenge. Reports have described similarities in clinical presentation, morphological appearances, and immunophenotypes; however, this distinction is significant, because the different entities vary in clinical course, prognosis, and management requirements . The presence of EBV‐encoded RNA significantly favours a PBL diagnosis (50–75%), although studies have shown that both immunocompetent and immunocompromised individuals may develop EBV‐driven extramedullary PCTs and DLBCLs .…”
Section: Introductionmentioning
confidence: 99%
“…Reports have described similarities in clinical presentation, morphological appearances, and immunophenotypes; however, this distinction is significant, because the different entities vary in clinical course, prognosis, and management requirements. [8][9][10] The presence of EBV-encoded RNA significantly favours a PBL diagnosis (50-75%), although studies have shown that both immunocompetent and immunocompromised individuals may develop EBV-driven extramedullary PCTs and DLBCLs. 11,12 However, these tumours are restricted to single case reports and small series, are usually well differentiated, and are not truly plasmablastic.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of PBL is unclear, but the importance of the Epstein‐Barr virus (EBV) is frequently speculated, as it is detected in 78% of cases . Moreover, due to the low incidence of this malignancy, very little is understood regarding PBL prognostic features, especially when it is diagnosed in the oral and maxillofacial region, impairing that a more appropriate therapeutic management can be applied for these patients .…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of this disease is difficult not only due to its unique immunophenotype but also due to several overlapping morphological and phenotypical features with plasmacytoma, plasmablastic myeloma, or diffuse large B‐cell lymphoma (DLBCL). Although there may be several distinguishing features that aid in differentiating these lymphoid tumors, a specific histopathological diagnosis is not always straightforward . Importantly, clinical correlation such as the presence of lymphadenopathy may favor the diagnosis of plasmablastic lymphoma over a plasma cell neoplasm and the presence of end‐organ damage; that is, CRAB criteria or plasma paraprotein may be more suggestive of multiple myeloma …”
Section: Discussionmentioning
confidence: 99%